The Interaction between Income Inequality and Imports of Manufactured Goods: A Case for Developing Countries - Fawaz, Fadi; Rahnamamoghadam, Masha (Journal of Income Distribution®, 2012)
Questions surrounding income inequality have received much attention in recent economic literature. The effects of the imports of manufactured goods on income inequality in developing countries are found to be inconclusive in the existing literature. This study proposes a “threshold effect” to address this issue. We argue that when imports benefit a large portion of population, a decrease in income inequality is more likely to occur within the country. We use a dynamic specification to estimate the impact of trade on within-country income inequality in a sample for low- and high-income, developing countries (LIDC and HIDC) over the period 1970-2009. We find that if the trade of manufactured goods is above (below) the threshold, income inequality will decrease (increase).